2020
DOI: 10.3390/ijerph17155575
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Influence of the COVID-19 Pandemic Lockdowns on Health Behaviors and Quality of Life among Chinese Adults

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has created challenges that have caused profound changes in health behaviors. This study aimed to explore how COVID-19 is affecting the health-related quality of life (QoL) among Chinese adults. Methods: The data of health-related behaviors and QoL were collected via online surveys from 2289 adults (mean age = 27.8 ± 12 years) who had been isolated at home for an average of 77 days. Results: More than 50% of the respondents reported that their time e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
198
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(241 citation statements)
references
References 34 publications
(36 reference statements)
19
198
1
10
Order By: Relevance
“…Furthermore, the number of active students decreased significantly in comparison to the situation before the COVID-19 outbreak in Ukraine, which is consistent with some previous studies [23,34,46,47]. Stanton et al [23] showed that negative physical activity changes are associated with increased depression, anxiety, and stress symptoms.…”
Section: Relationship Between Pa and Mental Healthsupporting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, the number of active students decreased significantly in comparison to the situation before the COVID-19 outbreak in Ukraine, which is consistent with some previous studies [23,34,46,47]. Stanton et al [23] showed that negative physical activity changes are associated with increased depression, anxiety, and stress symptoms.…”
Section: Relationship Between Pa and Mental Healthsupporting
confidence: 85%
“…The beneficial effect of PA on mental health is well-documented in many studies e.g., [34][35][36][37][38][39][40]. Regular exercise improves sleep, mood, endurance, and cardiovascular fitness; reduces cholesterol, body weight, tiredness; and helps boost stress relief, energy, and interest in sex.…”
Section: Physical Activity and Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…alcohol consumption). A Chinese survey found mixed effects of isolation in healthy behaviors, with increase in eating quality but less physical activity [28]. As expected, in our sample associations between these predictors and mental health were found, with a moderate effect of exercise routine.…”
Section: Discussionsupporting
confidence: 83%